2002
DOI: 10.1046/j.1365-2311.2002.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg cannibalism byColeomegilla maculata lengineonates: preference even in the presence of essential prey

Abstract: Abstract. 1. Egg cannibalism among coccinellids has been reported widely, however reasons why this type of behaviour is observed so frequently have been neglected. This experiment was undertaken to clarify whether cannibalistic behaviour is advantageous to Coleomegilla maculata lengi Thimberlake neonates and to understand the reasons for high levels of egg cannibalism.2. Benefits gained by neonate cannibals were ascertained by comparing survival, developmental time, and second-instar weight of C. maculata larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…It is generally assumed that eggs are highly nutritious, as they are provisioned by the mother with a yolk to feed the developing embryonic larva. Eggs could, therefore, be considered as a high quality food source that fits the nutritional requirements of neonates better than other diets (Eickwort 1973;Takahashi 1987;Hodek and Honek 1996;Gagnè et al 2002). Sometimes the survival of the 1st instar and its foraging success could be related to cannibalism (Banks 1956;Dixon 1959;Brown 1972;Kawai 1978), as this period is frequently critical and limiting for the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that eggs are highly nutritious, as they are provisioned by the mother with a yolk to feed the developing embryonic larva. Eggs could, therefore, be considered as a high quality food source that fits the nutritional requirements of neonates better than other diets (Eickwort 1973;Takahashi 1987;Hodek and Honek 1996;Gagnè et al 2002). Sometimes the survival of the 1st instar and its foraging success could be related to cannibalism (Banks 1956;Dixon 1959;Brown 1972;Kawai 1978), as this period is frequently critical and limiting for the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Search terms were "cannibalistic" or "cannibalism" combined with "preference," "choice," "heterospecific," "interspecific," "Manly's," and "Chesson." Empirical studies: Duelli (1981); Orr et al (1990); Leonardsson (1991); Streams (1992); Macpherson and Gordoa (1994); MacRae and Croft (1997); Baras et al (1999);Schausberger (1999); Walzer and Schausberger (1999) ;Gerber and Echternacht (2000); Schausberger and Croft (2000); Yasuda et al (2001); Gagné et al (2002); Santi et al (2003); Park et al (2005); Dörner et al (2007); Mahe et al (2007); Rudolf (2008); Byström et al (2013). nibalism on both complete diet shift and diet broadening LHIGP scenarios.…”
Section: Model Formulationmentioning
confidence: 99%
“…Larvae of the coccidophagous ladybird Exochomus fl avipes generally developed faster when fed on conspecifi c eggs than when fed on their usual prey, Dactylopius opuntiae (Geyer 1947 ). Similarly, Col. maculata larvae gained more weight by preying on conspecifi c eggs than on aphids (Gagn é et al 2002 ). Agarwala and Dixon (1992) found that conspecifi c eggs of A. bipunctata were superior to aphids as food for fourth instars; consumption of a greater biomass of aphids was required to support a given rate of growth.…”
Section: Consumption Of L Arvaementioning
confidence: 99%